The Relationship Among Spirituality, Fear, and Mental Health on COVID-19 Among Adults: An Exploratory Research - Rathakrishnan, Balan; Singh, Soon Singh Bikar; Yahaya, Azizi; Kamaluddin, Mohammad Rahim; Aziz, Siti Fardaniah Abdul (Frontiers in Psychology, 2022)
The novel Coronavirus disease (COVID-19) is impactful on all aspects of individuals’ lives, particularly mental health due to the fear and spirituality associated with the pandemic. Thus, purpose of this study was to identify the relationship between fear, spirituality, and mental health on COVID-19 among adults in Malaysia. This study also examines spirituality as a mediator in relationship between fear and mental health. The study involved around 280 adults in Malaysia. This research is a quantitative study. Data analysis method (SEM-PLS) been used for data analysis. Based on descriptive analysis, mental health questionnaire indicated that 60.0% of them are at a poor level of mental health while 57.5% of respondents showed a moderate level of COVID-19 fear, and 60.4% of respondents owned moderate level of spiritual well-being. The results also demonstrated that respondents that have a high level of fear would have a high level of mental health; interestingly, those with a high level of spirituality will have a lower level of mental health. Findings indicated that spirituality significantly mediated the relationship between fear and mental health. This research will help to demonstrate how important spirituality values to control mental health to be more positive among adults in Malaysia. The main contributions of this study are to help come out with new intervention method for those who are mentally ill and need help.